Autonomous Vehicle Acceptance in China: TAM-Based Comparison of Civilian and Military Contexts - Dan Wan; Ling Peng (World Electric Vehicle Journal)
In this study, a comparative analysis is conducted on the public acceptance of autonomous vehicles (AVs) in civilian and military contexts among the Chinese public. In order to identify the key factors influencing AV adoption under different scenarios, a Technology Acceptance Model (TAM) framework was applied in combination with an extended variable of perceived risk. Also, a structured questionnaire was designed, with 1004 valid responses received from a sample comprising mainly members of the Chinese public aged 31–50. Data analysis was conducted through reliability and validity tests, correlation analysis, and Structural Equation Modeling (SEM). Despite some slight variations in acceptance level between civilian and military fields, overall public attitudes are relatively consistent, according to the analytical results. Specifically, the average behavioral intention is slightly stronger and more consistent among the public in the civilian context, with higher scores achieved with respect to perceived usefulness and perceived risk in the military context, indicating a stronger emphasis on functionality and safety in military applications. As confirmed by SEM path analysis, there are significant influences exerted on behavioral intention by perceived usefulness, perceived ease of use, and satisfaction. These results demonstrate a high level of public acceptance of AV technology among the Chinese public in the context of policy support and technological innovation, providing empirical insights into the development of scenario-specific promotion strategies for the effective application of AV in various settings.